Forced convection heat transfer performance of porous twisted tape insert - Ahamed, J.U.; Bhuiya, M.M.K.; Saidur, Rahman; Masjuki, Haji Hassan; Sarkar, M.A.R.; Sayem, A.S.M.; Islam, M. (University of Malaya, 2010)
Heat transfer performance of porous twisted tape insert in a circular tube was experimentally investigated. Tube wall temperatures and pressure drops along the axial distance of the test section at steady state condition were measured for different flows having Reynolds number ranging from 1.4 x 104 to 5.2 x 104 for both the plain and the tube with porous twisted tape insert. Heat transfer coefficient, friction factor, and pumping power were calculated from the measured data. Heat transfer and fluid flow characteristics of the porous twisted tape inserted tube were explained from the measured and calculated values. Performance of the porous twisted tape inserted tube was also evaluated. The results showed for porous twisted tape inserted tube, the average heat transfer coefficient was 2.60 times higher, the heat flux was 1.55 times higher, the friction factor was 2.25 times higher and the pumping power was 2.0 times higher than those of plain tube values for similar flow conditions.